(untitled) (Fiep Bulletin - online, 2011)
Currently you can prove that the main problems faced in health organizations have been due to the funding system, some items such as misallocation of resources, inefficiency of management, rising costs and unequal conditions of access for users within the system. The study aims to analyze the screen in the current trends of publications and studies conducted on quality management in health. This is a study of its kind conducted by the systematic review literature on the theme of Health Management, Public Health Administration and Management of Health Services in the databases LILACS and MEDLINE. After applying the inclusion and exclusion criteria, we obtained a sample of 21 studies, 14 in LILACS and MEDLINE in July. Most studies were published in 2005 (28.57%) followed in 2006 and 2007 (19.4%). Among the publications found were 61.90% of the qualitative approach. Regarding the regions where the same were carried out to the southern region with 38.09% of the total followed by the southeast region with 33.33% of the sample. Thus it is concluded that rates of studies on the theme discussed is still new, so either impede research and readings about the topic.